Sport Science Publication of the International Tennis Federation (Coaching and Sport Science Review, 2009)
TALENT DEVELOPMENT IN TENNIS - SPEAKING THE LANGUAGE (Paul Roetert, Mark Kovacs and Miguel Crespo) TEACHING TENNIS TO DEAF CHILDREN (Janet Young and Anne Browne) GRAND SLAM MEN`S SINGLES TENNIS 1991-2009 SERVE SPEEDS AND OTHER RELATED DATA (Rod Cross and Graham Pollard) FIT TO PLAY & PERFORM -CORE TRAVEL TRAINING (Carl Petersen (CAN) and Nina Nittinger) STANDARDIZED TESTING OF FOREHAND AND BACKHAND GROUNDSTROKES IN TENNIS THROUGH A BIRD`S EYE PERSPECTIVE (Armin Kibele, Claudia Classen, and Kathrin Triebfuerst) BREATHING TO MANAGE ANXIETY IN TENNIS (Andrew Peden) THE GAME-BASED COACHING METHODOLOGY - AN INVESTIGATION OF PRINCIPLES AND PRACTICE (David Wilson) INDICATOR OF DEPTH FOR THE RETURN OF SERVE (Patrick Zawadzki and Josep Roca) THE KEYS TO MUSCLE WEIGHT GAIN FOR TENNIS PLAYERS (Page Love) THE TENNIS SOCIO ECONOMIC ACTIVITY IN FRANCE (Emmanuel Bayle and Lionel Maltese)